Cost of illness of Primary Biliary Cholangitis - a population-based study. Issue 9 (September 2021) - Gerussi, Alessio; Restelli, Umberto; Croce, Davide; Bonfanti, Marzia; Invernizzi, Pietro; Carbone, Marco
Abstract: Background: The economic burden of Primary Biliary Cholangitis (PBC) has not been investigated at population-level. Aim of this study was to estimate the cost of illness of PBC in Lombardy, Italy. Methods: Individuals with PBC were identified through ICD-9-CM code 571.6 and/or medical exemption code 008.571.6, from the Banca Dati Assistito of Lombardy. Only health services (outpatient, inpatient activities and drugs) related to PBC were considered to estimate direct medical costs in 2017. Results: We identified 970 adult patients (83.5% females) with a mean age of 61 years. Global annual costs were equal to € 913, 763 (€ 942 per patient), with € 459, 506 (50.3%, € 474 per patient) deriving from hospitalizations (mostly due to liver transplantation, 30.5%, and cirrhosis complications, 20.6%). Costs from outpatient activities were € 109, 090 (11.9%, € 112 per patient). Conclusions: This study provides an overview of the costs attributed to PBC care and management, mainly related to hospitalizations for cirrhosis complications, which is necessary for assuring cost-effective introduction of novel therapies. Additional studies focused on indirect cost, e.g. overall loss of productivity, are warranted.